2021
DOI: 10.1177/00224669211013354
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Benefits and Barriers to Postsecondary Education for Students With Intellectual and Developmental Disabilities

Abstract: Postsecondary educational programs (PSEs) are increasingly an option for students with intellectual and developmental disabilities (IDD). This scoping review synthesized research to understand the impacts of these programs for students with IDD and for campus, and barriers to these programs across stages of engagement (exploration, participation, completion). Studies were identified by searching PubMed, PsycINFO, ERIC, and Web of Science databases and reference lists of included articles. Twenty-one studies me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As the number of these higher education programs for students with ID has grown, studies have shown that studying at university is beneficial for students with ID [ 10 , 20 , 21 , 22 , 23 ]. These benefits include increased employment opportunities, social inclusion, independent living, and improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the number of these higher education programs for students with ID has grown, studies have shown that studying at university is beneficial for students with ID [ 10 , 20 , 21 , 22 , 23 ]. These benefits include increased employment opportunities, social inclusion, independent living, and improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, legislative changes in favor of students with ID at university and the reported benefits of this experience have led to an increase in the number of these students, as their families and they themselves see university as a viable opportunity for them [ 22 , 32 ]. Students with ID have several reasons for enrolling in higher education programs, including perceived social benefits, a desire to improve their chances of finding and securing paid employment, and the opportunity to make new friends, especially friends without disabilities [ 19 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students with significant support needs are less likely to enroll in postsecondary education and training programs, live independently, and are less likely to be competitively employed (Avellone et al, 2021;Lee & Taylor, 2022;Newman et al, 2011;Winsor et al, 2021). Overall, these students often face greater challenges in achieving their postschool goals and may require more specialized support to do so.…”
mentioning
confidence: 99%
“…Postschool outcomes for students with significant support needs tend to be poorer than those for students with less-intensive support needs (e.g., learning disabilities, physical disabilities, or language disorders; Newman, 2011). Students with significant support needs are less likely to enroll in postsecondary education and training programs, live independently, and are less likely to be competitively employed (Avellone et al, 2021; Lee & Taylor, 2022; Newman et al, 2011; Winsor et al, 2021). Overall, these students often face greater challenges in achieving their postschool goals and may require more specialized support to do so.…”
mentioning
confidence: 99%
“…For example, Biggs and Snodgrass (2020) interviewed 16 elementary school students who had friends with ESN, finding that the children described their friends by identifying their unique traits and strengths, and not by perceived deficits related to disability. Recent studies (see Athamanah et al, 2020; Gilson et al, 2020; Lee & Taylor, 2022; Travers et al, 2020) have found that college students without IDD who attended institutions of higher education with inclusive postsecondary education (IPSE) programs reported an increase in disability awareness and valuing the perspectives of people with IDD (see https://thinkcollege.net/ for information on IPSE opportunities). Similarly, adults who described spending time with their siblings with IDD characterized their relationship as positive (Lemoine & Schneider, 2022) and could identify their sibling’s strengths (Carter et al, 2020).…”
mentioning
confidence: 99%